Effects of background color and restoration depth on color adjustment potential of a new single-shade resin composite versus multi-shade resin composites - Zhu, Jiakang; Chen, Siyang; Anniwaer, Annikaer; Xu, Yue; Huang, Cui (Frontiers in Bioengineering and Biotechnology, 2023)
The objectives of this study this study was to evaluate the effects of background color and restoration depth on color adjustment potential of a new single-shade resin composite versus multi-shade resin composites. Two multi-shade resin composites (Spectrum TPH3 and Clearfil AP-X) marked A2 shade and a new single-shade resin composite (Charisma Diamond One) were tested. Four base shades (A1, A2, A3, and A3.5) of the same resin composite (Filtek Z250) were selected as different background colors. Dual specimens with 1-, 2-, and 3-mm restoration depth and single specimens of all materials were fabricated. CIE color coordinates were measured using a spectrophotometer, then color differences (∆E00) and translucency parameter (TP00) were calculated using the CIEDE2000 formula. Independent observers performed visual scoring. CAP-I and CAP-V values were calculated according to ΔE00 and visual scoring. The results revealed that CAP-I and CAP-V were significantly affected by resin composite type, background color, and restoration depth. CAP-I and CAP-V decreased as restoration depth increased at the same background color for all materials. Charisma Diamond One had the highest CAP-I and CAP-V values at all background colors and restoration depths, with the highest TP00 value. These findings demonstrated that color adjustment potential was dependent on resin composite type, background color, and restoration depth, so shade selection is indispensable for multi-shade resin composites. Charisma Diamond One exhibited the highest color adjustment potential and the most pronounced color shifting, contributing to simplifying the process of shade selection and improving the efficiency of clinical work.* or # indicates no statistical difference among the material types at the same background color and type/restoration depth of specimen (p > 0.05).